Pengaruh Gaya Hidup Konsumtif, Edukasi Keuangan, dan Motivasi Pengelolaan Keuangan terhadap Perilaku Pengelolaan Keuangan Mahasiswa (Jurnal Kendali Akuntansi, 2023)
This research aims to analyze the influence of consumerist lifestyle, financial education, and financial management motivation on financial management behavior among accounting students at Majapahit Islamic University. Financial issues are a common problem faced by every individual, and this study examines whether the observed problems are influenced by the variables under investigation. The population of this study consists of accounting students from the 2019, 2020, 2021, and 2022 cohorts at Majapahit Islamic University, totaling 80 respondents. The research employs a quantitative approach using primary data collected through questionnaires distributed to the respondents. The data analysis technique used in this study is multiple linear regression.The results of this study indicate that consumerist lifestyle, financial education, and financial management motivation have a positive influence on the financial management behavior of students at Majapahit Islamic University. This suggests that higher consumerist lifestyle, better financial education received, and stronger motivation to manage finances result in better financial management behavior among the university students.